Answer:
3x+12
Step-by-step explanation:
You need to do 3 times x which equals 3x and then do 3 times 4 and get 12 so it ends up as 3x+12
hope this helps
stay safe:)))
brainliest is appreciated
this person keeps copying and reporting my questions and then saying i copied them so im sorry if that happens :(
Answer:
kkk
Step-by-step explanation:
Answer:
-1
Step-by-step explanation:
Plug 7 in for wherever there's an "x."
f(x) = 2(7) - 6
f(x) = 14 - 6
f(x) = 8
Now subtract 9 from 8.
8 - 9 = -1
Step-by-step explanation:
Simplify the left side:
5x - 20 = 3x + 4
Move all terms containing x to the left side of the equation:
2x - 20 = 4
Move all terms not containing x to the right side of the equation:
2x = 24
Divide each term by 2 and simplify:
x = 12